Leptin induced changes in sperm parameters in spraguedawley rats: role of oxidative stress and its prevention by melatonin / Fayez A. M. Almabhouh - A. M. Almabhouh, Fayez (Institute of Graduate Studies, UiTM, 2016)
Exogenous leptin administration has been shown to adversely effect sperm count and sperm morphology in normal adult rats. It is however unknown if it affects sperm DNA integrity and increases apoptosis of sperm and testicular tissue cells. This study therefore investigated the effect of leptin administration on sperm count, morphology, sperm DNA integrity, sperm DNA damage, apoptosis and histone-to-protamine ratios and its prevention by melatonin in Sprague-Dawley rats. It also examined the reversal of these effects on sperm parameters for up to 56 days following cessation of leptin treatment. Seventy-eight male Sprague-Dawley rats, aged 12 weeks, were randomized into 13 groups, Group 1 rats acted as a control and were given saline. Group 2 rats were given 60 μg/kg body weight daily of leptin for 42 days. Group 3 (leptin-melatonin-10) rats were given 60 μg/kg/day of leptin and 10 mg of melatonin/day/kg body weight in drinking water. Group 4 (leptin-melatonin-20) rats were given 60 μg/kg/day of leptin and 20 mg of melatonin/day/kg body weight in drinking water. Group 5 (melatonin-10) rats were given 10 mg of melatonin/day/kg body weight in drinking water. The remaining 8 groups were divided into four leptin and four saline treated control groups to examine the reversal of adverse effects of leptin…